A hydrophobic filter confers the cation selectivity of Zygosaccharomyces rouxii plasma-membrane Na+/H+ antiporter - Kinclova-Zimmermannova, Olga; Falson, Pierre; Cmunt, Denis; Sychrova, Hana (Journal of molecular biology, 2015)
Na(+)/H(+) antiporters may recognize all alkali-metal cations as substrates but may transport them selectively. Plasma-membrane Zygosaccharomyces rouxii Sod2-22 antiporter exports Na(+) and Li(+), but not K(+). The molecular basis of this selectivity is unknown. We combined protein structure modeling, site-directed mutagenesis, phenotype analysis and cation efflux measurements to localize and characterize the cation selectivity region. A three-dimensional model of the ZrSod2-22 transmembrane domain was generated based on the X-ray structure of the Escherichia coli NhaA antiporter and primary sequence alignments with homologous yeast antiporters. The model suggested a close proximity of Thr141, Ala179 and Val375 from transmembrane segments 4, 5 and 11, respectively, forming a hydrophobic hole in the putative cation pathway's core. A series of mutagenesis experiments verified the model and showed that structural modifications of the hole resulted in altered cation selectivity and transport activity. The triple ZrSod2-22 mutant T141S-A179T-V375I gained K(+) transport capacity. The point mutation A179T restricted the antiporter substrate specificity to Li(+) and reduced its transport activity, while serine at this position preserved the native cation selectivity. The negative effect of the A179T mutation can be eliminated by introducing a second mutation, T141S or T141A, in the preceding transmembrane domain. Our experimental results confirm that the three residues found through modeling play a central role in the determination of cation selectivity and transport activity in Z. rouxii Na(+)/H(+) antiporter and that the cation selectivity can be modulated by repositioning a single local methyl group.
Keywords: Models, Molecular; substrátová specifita; bodová mutace; Sodium; Amino Acid Sequence; molekulární sekvence - údaje; konformace proteinů; sodík; substrate specificity; kationty; Cations; sekvence aminokyselin; Lithium; Molecular Sequence Data; Fungal Proteins; yeast; lithium; Zygosaccharomyces; Potassium; Substrate Specificity; fungální proteiny; plasma membrane; sodium proton exchanger; Point Mutation; draslík; Hydrophobic and Hydrophilic Interactions; molekulární modely; potassium transport; hydrofobní a hydrofilní interakce; Na(+)-H(+) antiport; Sodium-Hydrogen Exchangers; Protein Conformation